Comparative spermatozoal ultrastructure and molecular analysis in dromiid crabs and their phylogenetic implications for Dromiidae and Podotremata (Decapoda: Brachyura). Issue 6 (November 2018) - Garcia Bento, Maria Alice; Miranda, Ivana; Mantelatto, Fernando Luis; Zara, Fernando José
Abstract: We described the spermatozoal ultrastructure and conducted a molecular analysis of Dromiidae Hypoconcha parasitica, Hypoconcha arcuata, Moreiradromia antillensis and Dromia erythropus . To elucidate the relationship between the different species of this brachyuran group, we also compared the spermatozoal morphologies and phylogenetic positioning among species of Dromiidae, Dromioidea and Podotremata. Specimens were collected from the northern coast of São Paulo, Brazil and were fixed and processed followed by transmission electron microscopy and molecular analysis routines. The Dromiidae spermatozoa studied are characterized by a discoidal acrosome, with three or four concentric zones, which are centrally separated by a bilaterally capitate perforatorial chamber, with a "mushroom"-shaped apex in the Hypoconchinae and a "T-shape" in Dromiinae. Above the perforatorial chamber, there is an apical protuberance, continuous with the subopercular region and the operculum, which forms a low, centrally perforated dome. Under differential interference contrast microscopy, the spermatozoa show 3 to 4 radial arms. The spermatozoal characters in Hypoconchinae and Dromiinae do not separate these subfamilies from the Dromiidae and Dromioidea. Ultrastructural differentiation was only found between representative Dromioidea and other Podotremata. Thus, the spermiotaxonomy of these Hypoconcha, Moreiradromia and Dromia species corroborated previous morphological and molecular studies, supporting the monophyly of Dromiidae and Dynomenidae in relation to Homolidae and Latreilliidae. Graphical abstract: Highlights: The Dromiidae spermatozoa are typically podotreme in overall shape ultrastructure. No ultrastructural characters are found to separate Dromioidea families. The perforatorial chamber apex is the character to separate Dromiidae subfamilies. Ultrastructural differences only separate Dromioidea from the other Podotremata. Raninidae appears as the most external clade to all the other Pododremata.